(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Molding materials play a key role in prosthetic dentistry, especially in the manufacture of cast metal structures. The quality of the casting mold directly affects the accuracy, strength, and clinical efficacy of orthopedic restorations. Modern casting technologies place high demands on the physical and chemical characteristics of molding materials.